¿CÓMO PERCIBEN LAS UNIVERSIDADES EL FOMENTO DEL EMPRENDIMIENTO? - Pérez Palacios, Emma (2012)
This paper presents some of the results of the "Promotion of Youth Entrepreneurship in College" 2010. This study reports the contributions of 9 centers of higher education and 5 public and private institutions linked to the promotion of entrepreneurship. In this opportunity we present the position of the centers of higher education regarding the importance of promoting entrepreneurship. The study reveals that the promotion of entrepreneurship is an action considered IMPORTANT, despite this classification, the top training centers are not using this issue as a strategy of differentiation and market positioning. It also identifies the main reasons why young students of higher education centers are not attracted to the entrepreneurial challenge are: a) expectations about economic growth in the country, a product which would require the labor market labor dependent skilled labor in certain sectors, b) risk aversion, c) lack of knowledge about how and in which sector to start a business, and d) lack of capital.